Terraformings - Bruyere, Vincent (Imaginations, 2019)
Terraforming, or planetary engineering, is a speculative domain of activity entertaining colonial solutions to extreme disaster and systemic crises in the age of spatial exploration. Since the 1940s, terraforming has provided an extremely fertile playground for science fiction writers, whose terraformed worlds have blown up to planetary dimensions the historical and narrative contours of a novelistic tradition born at the beginning of the eighteenth century on Robinson Crusoe’s island. It is my contention that the speculative existence of terraformed worlds is always already informed by a cultural memory of oikos—the inhabited world. No less experimental in tone and intent than terraforming itself, this paper seeks to transform terraforming into a critical tool in visual culture: a mode of handling texts and images whose temporal parameters exceed that of traditional historiography.